Virtual Power Plant. Environmental Technology Management Tools of The Settlement Processes - Sibilla, Maurizio (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The Distributed Energy Resource (DER) systems represent a possible option for the implementation of the Low Carbon Cities development scenario, consistently with EU orientations. Many surveys, especially of engineering and information technology origin, are contributing to DER systems spread through testing the Virtual Power Plan (VVP): a technological system aimed at synchronously managing the information and energy fluxes, and able to have an effect on the urban metabolism balance and on the energy chain organizational model.  In the event of a wider VVP spread, consequences for the urban structure social and technical conversion process might be envisioned. Such systems gain importance in terms of starting urban renewal processes, introducing new rules for the local energy and environmental infrastructures.  In this way, it is envisioned the need for a deeper comprehension of the VVP innovative functionalities, this comprehension being significant for all the branches of knowledge which are interested in developing methods and tools for the Environmental Technology Management and Planning of the settlement processes.  The author, who is interested in producing and organizing an energy, distributed, renewable and interactive model, shows, through a critical analysis of the Electricity Networks Europe program study cases, the operating potential of the new system, emphasizing the consequences on the settlement process development, thus providing a first definition of the strategic features for the VVP technical and social implementation.